Contribution of pain to subsequent cognitive decline or dementia: A systematic review and meta-analysis of cohort studies. (February 2023) - Yuan, Hui; Ahmed, Wali Lukman; Liu, Mengdie; Tu, Shumin; Zhou, Fang; Wang, Shuo
Abstract: Background: Dementia is an urgent public health problem worldwide, and the determination of the contribution of pain to cognitive decline or dementia is significant for the prevention of dementia. Objective: To comprehensively explore the contribution of pain to subsequent cognitive decline or dementia and analyze possible influencing factors. Design: Systematic review and meta-analysis of cohort studies. Methods: We systematically searched MEDLINE, EMBASE, PsycINFO, CINAHL, Cochrane Library, China National Knowledge Internet, WANFANG DATA and VIP for cohort studies from database inception to January 21, 2022. Random-effects meta-analysis was used to pool odds ratios (ORs) and 95% confidence intervals (CIs) of incident cognitive decline or dementia among patients with pain. Subgroup analyses and meta-regression were used to explore the sources of heterogeneity. Results: A total of 35 cohort studies containing 1, 122, 503 participants were included. As a whole, pain (OR = 1.24; 95% CI = 1.17–1.31) was a risk factor for subsequent cognitive decline or dementia; headache, migraine, tension-type headache, widespread pain, and irritable bowel syndrome, but not burning mouth syndrome, were also risk factors. Pain increased the risk of all-cause dementia (OR = 1.26; 95% CI = 1.18–1.35), Alzheimer's disease (OR = 1.28; 95% CI = 1.12–1.47), and vascular dementia (OR = 1.31; 95% CI = 1.06–1.62). Pain interference (OR = 1.42; 95% CI = 1.16–1.74) was associated with an increased risk of cognitive decline or dementia, while pain intensity was not. Pooled results from studies with sample sizes less than 2000 or with relatively low quality showed that pain did not increase the risk of cognitive decline or dementia. There was no statistically significant increase in the risk of cognitive decline or dementia in people with pain aged ≥ 75 years. Conclusions: Our results demonstrated that pain increased the risk of subsequent cognitive decline or dementia. Sample size, study methodological quality, types of pain, pain severity (pain interference), and age composition of the study population may affect the relationship between pain and cognitive decline or dementia. Registration: PROSPERO (CRD42022316406).